Sedative-sparing effect of acupuncture in gastrointestinal endoscopy: systematic review and meta-analysis - Yang, Yun; Ji, Haiyang; Lu, Yunqiong; Hong, Jue; Yang, Guang; Kong, Xiehe; Liu, Jie; Ma, Xiaopeng (Frontiers in Medicine, 2023)
Objective: This study aimed to perform a systematic review and meta-analysis to identify the efficacy of acupuncture therapy (including manual acupuncture and electroacupuncture) performed before or during gastrointestinal endoscopy with propofol as the main sedative, compared with placebo, sham acupuncture, or no additional treatment other than the same sedation. Methods: A systematic search was performed through PubMed, Embase, Web of Science and Cochrane Library, Chinese Biomedical Databases (CBM), Wanfang database, China National Knowledge Infrastructure (CNKI), SinoMed, and Chinese Scientific Journal Database (VIP) to collect randomized controlled trials published before 5 November 2022. Bias assessment of the included RCTs was performed according to the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). Stata16.0 software was used to perform statistical analysis, sensitivity analysis, and publication bias analysis. The primary outcome was sedative consumption, and the secondary outcomes included the incidence of adverse events and wake-up time. Results: A total of 10 studies with 1331 participants were included. The results showed that sedative consumption (mean difference [MD]=-29.32, 95%CI[-36.13, -22.50], P<0.001), wake-up time(MD=-3.87, 95%CI[-5.43, -2.31], P<0.001) and the incidence of adverse events including hypotension, nausea and vomiting, and coughing (P＜0.05) were significantly lower in the treatment group than in the control group. Conclusion: Acupuncture combined with sedation reduces sedative consumption and wake-up time compared with sedation alone in gastrointestinal endoscopy; this combined approach allows patients to regain consciousness more quickly after examination and lower the risk of adverse effects. However, with the limited quantity and quality of relevant clinical studies, caution must be applied until more high-quality clinical studies verify and refine the conclusions. Systematic Review Registration: PROSPERO [CRD42022370422].